Diabetes and pre-diabetes among adults reaching health centers in Luanda, Angola: prevalence and associated factors - Robbiati, Claudia; Putoto, Giovanni; Da Conceição, Natália; Armando, António; Segafredo, Giulia; Atzori, Andrea; Cavallin, Francesco (Scientific reports, 2020)
With the lack of surveys, surveillance program and/or statistical data, epidemiologic studies can provide a better understanding of diabetes in Sub-Saharan Africa. This was a cross-sectional survey to determine prevalence of diabetes and impaired fasting glucose (IFG) among adults attending six health centres in six different districts of Luanda (Angola) during August-November 2018, followed by a case-control study to assess the risk factors for IFG and diabetes in a subgroup of subjects not receiving treatment for diabetes. Factors associated with diabetes/IFG were assessed using a generalized ordered logit model and the effects were expressed as odds ratios (OR 1 for IFG/diabetes vs. no IFG/diabetes; OR 2 for diabetes vs. no diabetes) with 95% CI (confidence interval). Some 1,803 participants were included in the survey. Prevalence of diabetes was 12.0% (95%CI 10.5% to 13.5%) and prevalence of IFG was 9.0% (95%CI 7.7% to 10.4%). Older age (OR 1 = OR 2 1.03, 95%CI 1.02 to 1.04), higher weight (OR 1 = OR 2 1.01, 95%CI 1.01 to 1.03), having measured glycaemia before (OR 2 2.07, 95%CI 1.29 to 3.31), feeling polyuria (OR 1 1.93, 95%CI 1.13 to 3.28; OR 2 2.18, 95%CI 1.32 to 3.59), feeling polydipsia (OR 1 1.92, 95%CI 1.16 to 3.18), feeling weakness (OR 1 = OR 2 2.22, 95%CI 1.39 to 3.55), consumption of free-sugars food/beverages (OR 1 = OR 2 2.34, 95%CI 1.44 to 3.81) and time spent seated (OR 1 1.80, 95%CI 1.17 to 2.76) were associated with increased likelihood of diabetes and/or IFG, while eating vegetables was associated with decreased likelihood of IFG or diabetes (OR 1 = OR 2 0.69, 95%CI 0.47 to 0.99). In conclusion, the high prevalence of diabetes and IFG, with common unawareness of the disease, calls for appropriate interventions in Angolan urban settings. Further research may evaluate the impact of context-specific factors to enhance intervention strategies and feed the results into local health policies. In addition, such information may be useful for selecting high-risk subjects to test.